Genetic divergence between coffee genotypes resistant to rust based on anatomical features - Viana, Mariana Thereza Rodrigues; Gama, Tamara Cubiaki Pires da; Guedes, Janine Magalhães; Guimarães, Rubens José; Azevedo, Harianna Paula Alves de; Castanheira, Dalyse Toledo; Naves, Vicente Luiz (Revista de Ciências Agroveterinárias, 2018)
The objective of this study was to evaluate the genetic divergence of coffee genotypes resistant to rust, of the Germplasm Bank from Minas Gerais, based on anatomical features. A total of 12 foliar anatomical characteristics were assessed, and Mahalanobis distance was used to quantify the genetic divergence between genotypes. The Tocher method and the hierarchical method of UPGMA (Unweighted Pair-Group Method Using Arithmetic Averages) were used as group strategy. Moreover, relative contribution analyses of the variables were made. There was genetic variability between genotypes, and the analysis of Tocher and UPGMA grouping separated the genotypes into five and seven distinct groups, respectively. The MG 0582 genotype stood out as the most divergent based on the evaluated anatomical features. There is great genetic variability for the characteristics of foliar anatomy among the 15 genotypes evaluated, allowing to select superior genotypes based on these characteristics.